Germline RAD51C mutations in ovarian cancer susceptibility. (23rd July 2012) - Coulet, F; Fajac, A; Colas, C; Eyries, M; Dion‐Minière, A; Rouzier, R; Uzan, S; Lefranc, J‐P; Carbonnel, M; Cornelis, F; Cortez, A; Soubrier, F
Abstract Several genes might explain BRCA1/2 negative breast and ovarian family cases. Deleterious mutations in few genes involved in the Fanconi complex are responsible for Fanconi anemia at the homozygous state and breast cancer (BC) susceptibility at the heterozygous state (BRCA2, PALB2, BRIP1). RAD51C plays an important role in the double‐strand break repair pathway and a biallelic missense mutation in the RAD51C gene was found in a Fanconi anemia‐like disorder. Subsequently, six monoallelic pathogenic mutations were identified after screening 480 BRCA1/2 negative breast and ovarian cancer (BC/OC) pedigrees. Several reports were unsuccessful to replicate these results. To investigate whether germline mutations in RAD51C are associated with an increased risk of developing BC/OC, we screened, by Sanger sequencing of the coding sequence, 117 index cases of breast and ovarian families from French or European origin, and negative for BRCA1/2 mutations. In our study, we found 3 pathogenic mutations among 117 families screened which corresponds to a 2.6% frequency. Our results confirm that RAD51C is a susceptibility gene for ovarian and BC and that this gene should be screened for mutations in families with multiple BC/OC.